1989
DOI: 10.1099/0022-1317-70-7-1921
|View full text |Cite
|
Sign up to set email alerts
|

Retrovirus-induced Cell Fusion Is Enhanced by Protease Treatment

Abstract: SUMMARYThe effect of proteases on retrovirus-induced cell fusion was studied. Both 'fusion from within' (fusion between infected and uninfected cells) and 'fusion from without' (fusion of uninfected cells by virus addition) was enhanced after treatment with proteases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…Furthermore, these basic amino acids are likely to occur on the surface of the protein (Birdi, 1989). We have previously shown that cleavage of gp70 might be important for membrane fusion and infection (Andersen, 1987;Andersen & Skov, 1989). Similar results have been indicated for HIV gpl20 (Clement et al, 1991 putative cleavage may be caused by a trypsin-like protease as infection can be inhibited by leupeptin and antipain (Andersen, 1983).…”
Section: Introductionsupporting
confidence: 64%
“…Furthermore, these basic amino acids are likely to occur on the surface of the protein (Birdi, 1989). We have previously shown that cleavage of gp70 might be important for membrane fusion and infection (Andersen, 1987;Andersen & Skov, 1989). Similar results have been indicated for HIV gpl20 (Clement et al, 1991 putative cleavage may be caused by a trypsin-like protease as infection can be inhibited by leupeptin and antipain (Andersen, 1983).…”
Section: Introductionsupporting
confidence: 64%
“…Host cell-determined routes of virus entry have not been observed for other enveloped viruses, in which the pH dependence is solely a property of the viral envelope glycoproteins. One explanation for the unusual phenomenon with XC cells might be the expression of a cell surface proteinase able to cleave the gp70 glycoprotein of MLV-E. Andersen (1985Andersen ( , 1987 has reported that gp70 is cleaved during MLV-E entry, and that MLV-Einduced cell fusion is enhanced by exogenous proteinase treatment (Andersen & Skov, 1989). It is likely that gp70 cleavage is a required post-adsorption step in the entry of MLV-E into cells (Andersen & Skov, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the unusual phenomenon with XC cells might be the expression of a cell surface proteinase able to cleave the gp70 glycoprotein of MLV-E. Andersen (1985Andersen ( , 1987 has reported that gp70 is cleaved during MLV-E entry, and that MLV-Einduced cell fusion is enhanced by exogenous proteinase treatment (Andersen & Skov, 1989). It is likely that gp70 cleavage is a required post-adsorption step in the entry of MLV-E into cells (Andersen & Skov, 1989). In that case, one could postulate that the activity of the proteinases that cleave MLV gp70 normally may be dependent on the low pH of endosomes in most cells, and hence is sensitive to weak bases such as NH~CI.…”
Section: Discussionmentioning
confidence: 99%
“…The transition of immature TM to its fusogenic form involves proteolytic cleavage of 16 amino acid residues at the carboxyl terminus of TM, or glycoprotein 15, to a truncated and active glycoprotein 12. The fusion process of various retroviruses is reportedly affected by changes in pH, 9 protease activity, 10 and amphotericin B, 11 or by growth in murine XC cells. 12 The ability of cells to survive retroviral infections is apparently facilitated by the controlled maturation of wild-type TM after the virus leaves the cell.…”
mentioning
confidence: 99%